We have to factorize f=x^3 + 4x^2 - 7x - 10

f=x^3 + 4x^2 - 7x - 10

=> x^3 + 6x^2 - 2x^2 + 5x - 12x - 10

=> x^3 + 6x^2 + 5x - 2x^2 - 12x - 10

=> x(x^2 + 6x +5) - 2(x^2 +...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to factorize f=x^3 + 4x^2 - 7x - 10

f=x^3 + 4x^2 - 7x - 10

=> x^3 + 6x^2 - 2x^2 + 5x - 12x - 10

=> x^3 + 6x^2 + 5x - 2x^2 - 12x - 10

=> x(x^2 + 6x +5) - 2(x^2 + 6x + 5)

=> (x - 2) ( x^2 + 6x +5)

=> (x - 2)(x^2 + 5x +x +5)

=> (x - 2)(x(x +5) +1( x + 5))

=> (x - 2)(x +5) (x +1)

Therefore x^3 + 4x^2 - 7x - 10 = **(x - 2)(x +5) (x +1)**